2008
DOI: 10.1128/iai.00733-08
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 2 Recognition of the MicrosporidiaEncephalitozoonspp. Induces Nuclear Translocation of NF-κB and Subsequent Inflammatory Responses

Abstract: Microsporidia are obligate intracellular parasites that are ubiquitous in nature and have been recognized as causing an important emerging disease among immunocompromised individuals. Limited knowledge exists about the immune response against these organisms, and virtually nothing is known about the receptors involved in host recognition. Toll-like receptors (TLR) are pattern recognition receptors that bind to specific molecules found on pathogens and signal a variety of inflammatory responses. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 43 publications
1
23
2
Order By: Relevance
“…Almost all TLRs can deliver signal to MyD88. But recent research has found that TLR2, TLR3, and TLR4 can be independent of MyD88 to transfer signal (Fischer et al 2008;Gao et al 2012). In this investigation, HDRsEf1 was not able to increase the MyD88 in mRNA and protein levels, which suggests that HDRsEf1 activates inflammatory response independently of MyD88, which should be confirmed by further study.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Almost all TLRs can deliver signal to MyD88. But recent research has found that TLR2, TLR3, and TLR4 can be independent of MyD88 to transfer signal (Fischer et al 2008;Gao et al 2012). In this investigation, HDRsEf1 was not able to increase the MyD88 in mRNA and protein levels, which suggests that HDRsEf1 activates inflammatory response independently of MyD88, which should be confirmed by further study.…”
Section: Discussionsupporting
confidence: 60%
“…The presence of various asterisks (*, **, and ***) indicates statistical differences with significant levels of p < .05, p < .01, and p < .001, respectively. (Fischer et al 2008). In order to determine whether HDRsEf1 regulates the inflammatory response through MyD88, 1 × 10 8 CFU/mL of HDRsEf1 in DMEM was used to stimulate HT-29 cells, mRNA and protein levels of MyD88 from HT-29 cells were tested by qRT-PCR and Western blot, respectively.…”
Section: The Mrna and Protein Levels Of Myd88 In Ht-29 Stimulated By mentioning
confidence: 99%
“…Recent in vitro studies have demonstrated that E. cuniculi infection upregulates the TLR2 message in human monocyte-derived macrophages (11). However, no increase in the TLR4 message was observed in this study (11). Although a role for TLR2 in activation of DC during E. cuniculi was not observed in our study, it is possible that TLR2 may be involved in activation of other antigen-presenting cells, like macrophages, as reported in previous studies (3).…”
Section: Discussioncontrasting
confidence: 54%
“…The altered immune response in these mutant animals was attributed to enhancement of the regulatory T-cell response by commensal DNA in the intestinal tissues and/or to the inability of the mice to generate optimal effector T-cell immunity (16). Recent in vitro studies have demonstrated that E. cuniculi infection upregulates the TLR2 message in human monocyte-derived macrophages (11). However, no increase in the TLR4 message was observed in this study (11).…”
Section: Discussioncontrasting
confidence: 44%
“…22 In addition, NF-B translocation and subsequent inflammatory responses have been shown to be mediated via TLR2. 29 However, whether these signaling molecules participating in cPLA 2 and COX-2 expression induced by LTA in HTSMCs are still unknown. Thus, we investigated the roles of TLR2, MyD88, PI3K/Akt, Rac1, MAPKs, and NF-B in regulating LTA-induced cPLA 2 and COX-2-dependent airway inflammation in in vitro and in vivo.…”
mentioning
confidence: 99%